Flashblood: Blood sharing among female injecting drug users in Tanzania - McCurdy, Sheryl A. (Addiction, 2010)
AIMS: This study examined the association between the blood-sharing practice “flashblood” and demographic factors, HIV status, and variables associated with risky sex and drug behaviors among female injecting drug users. Flashblood is a syringe full of blood passed from someone who has just injected heroin to someone else who injects it in lieu of heroin. DESIGN: A cross-sectional study. SETTING: Dar es Salaam, Tanzania. PARTICIPANTS: One hundred and sixty-nine female injecting drug users (IDUs) were recruited using purposive sampling for hard-to-reach populations. MEASUREMENTS: The association between flashblood use, demographic and personal characteristics and risky sex and drug use variables was analyzed by t-test and χ(2) test. The association between flashblood use and residential neighborhood was mapped. FINDINGS: Flashblood users were more likely to: be married (p=.05), have lived in the current housing situation for a shorter time (p<.000), have been forced as a child to have sex by a family member(p=.007), inject heroin more in the last 30 days (p=.005), smoke marijuana at an earlier age (p=.04), use contaminated rinse-water (p<.03), pool money for drugs (p<.03), and share drugs (p=.00). Non-flashblood users were more likely to live with their parents (p=.003). Neighborhood flashblood use was highest near downtown and in the two next adjoining suburbs and lowest in the most distant suburbs. CONCLUSIONS: These data indicate that more vulnerable women who are heavy users and living in shorter term housing are injecting flashblood. The practice of flashblood appears to be spreading from the inner city to the suburbs.